Interaction between technology and recruiting practices - Vera Brencic (IZA World of Labor, 2021)
Employers are steadily increasing their reliance on technology when recruiting. On the one hand, this technology enables the wide dissemination of information and the management of large quantities of data at a relatively low cost. On the other hand, it introduces new costs and risks. The ease with which information can be shared, for example, can lead to its unauthorized use and obsolescence. Recruiting technologies are also susceptible to misuse and to biases built into their underlying algorithms. Better understanding of these trade-offs can inform government policies aiming to reduce search frictions in the labor market.
Keywords: J23; J33; L86; M52; 330; recruitment; internet; employment websites; social media sites; artificial intelligence